Penerapan Kecerdasan Majemuk Dalam Pembelajaran - Ibrahim Ibrahim; Maya Nur Solekha; Rabial Kanada; Kris Setyaningsih; Zulkipli Zulkipli (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to understand the latest developments in 21st century education with a focus on the theory of multiple intelligences, educational technology, and the values ​​of social justice and equity. Through the method of literature review, this study found that inclusive and holistic approaches in education are increasingly important. The theory of multiple intelligences became popular as a response to this need, valuing the diversity of intelligences in the process of teaching and learning. Educational technology and games have also been shown to support soft skill development and student participation. The values ​​of social justice and equity emerge as important elements in educational practices and policies. This study suggests further research on optimizing practices based on the theory of multiple intelligences, the effectiveness of technology-based educational games, and the integration of social justice and equity values ​​in education.